A mapping approach for real time imitation of human movements by a 22 DOF humanoid - Cornejo-Arismendi V.A. (2018)
This work was supported by grant 234-2015-FONDECYT (Master Program) from Cienciactiva of the National Council for Science,Technology and Technological Innovation (CONCYTEC-PERU).